2016
DOI: 10.1016/j.ejvs.2015.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Aortoiliac Anatomy After Elective Treatment of Infrarenal Abdominal Aortic Aneurysms with a Sac Anchoring Endoprosthesis

Abstract: Most aortoiliac anatomic characteristics remained unchanged post-EVAS. Filling of the endobags to a pressure of 180 mmHg may lead to lost thrombus volume in some patients, probably because liquid is squeezed into lumbar or the inferior mesenteric artery. The absolute differences in pre- and post-EVAS aortoiliac lengths were small, so pre-operative sizing is accurate for determining stent length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Previous reports have also shown there were only slight changes in aortic angulation after repair with the Nellix device. 10 Conventional EVAR endografts have inherent axial and bending stiffness, in addition to the stiffness of the guidewire, that straighten the aorta to a greater extent. 11 Furthermore, since conventional EVAR endografts have inherent flexibility, they may undergo more significant cyclic bending or angulation in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have also shown there were only slight changes in aortic angulation after repair with the Nellix device. 10 Conventional EVAR endografts have inherent axial and bending stiffness, in addition to the stiffness of the guidewire, that straighten the aorta to a greater extent. 11 Furthermore, since conventional EVAR endografts have inherent flexibility, they may undergo more significant cyclic bending or angulation in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, endovascular aneurysm sealing (EVAS) has been increasingly used for endovascular repair of AAAs, revision procedures, and iliac aneurysms. [5][6][7] Similar to traditional stent-graft EVAR, EVAS with sac-filling polymer technology has shown good early results when combined with parallel snorkel stents. 8 Despite these favorable early outcomes for snorkel endovascular aneurysm sealing (Sn-EVAS), there are still questions about medium-to long-term durability, which is undoubtedly related to device-tissue interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that intraluminal thrombus cannot be addressed as a rigid structure and might change over time. [11][12][13] This spongelike effect in combination with a larger AAA diameter might result in bending of the stent frames into the thrombus and parting of the stent frames, which can make the EVAS configuration unstable. A low amount of polymer surrounding the stent frames in small flow lumens might also induce instability into the EVAS configuration.…”
Section: Discussionmentioning
confidence: 99%